Adrenocortical carcinoma and succinate dehydrogenase gene mutations: an observational case series. Issue 5 (November 2017) - Else, Tobias; Lerario, Antonio Marcondes; Everett, Jessica; Haymon, Lori; Wham, Deborah; Mullane, Michael; Wilson, Tremika LeShan; Rainville, Irene; Rana, Huma; Worth, Andrew J; Snyder, Nathaniel W; Blair, Ian A; et al.
Abstract : Objective: Germline loss-of-function mutations in succinate dehydrogenase ( SDHx ) genes results in rare tumor syndromes that include pheochromocytoma, paraganglioma, and others. Here we report a case series of patients with adrenocortical carcinoma (ACC) that harbor SDHx mutations. Patients and results: We report four unrelated patients with ACC and SDHx mutations. All cases presented with Cushing syndrome and large adrenal masses that were confirmed to be ACC on pathology. All four ACC specimens were found to have truncating mutations in either SDHC or SDHA, while cases 1, 2 and 3 also had the mutations confirmed in the germline: Case 1: SDHC c.397C > T, pR133X; Case 2: SDHC c.43C > T, p.R15X; Case 3: SDHA c.91C > T, p.R31X; Case 4: SDHA c.1258C > T, p.Q420X. Notably, Case 1 had a father and daughter who both harbored the same SDHC germline mutation, and the father had a paraganglioma and renal cell carcinoma. A combination of next generation sequencing, and/or immunohistochemistry, and/or mass spectroscopy was used to determine whether there was loss of heterozygosity and/or loss of SDH protein expression or function within the ACC. Potential evidence of loss of heterozygosity was observed only in Case 2. Conclusions: We observed truncating mutations in SDHA or SDHC in the ACC and/or germline of four unrelated patients. Given how statistically improbable the concurrence of ACC and pathogenic germline SDHx mutations is expected to be, these observations raise the question whether ACC may be a rare manifestation of SDHx mutation syndromes. Further studies are needed to investigate the possible role of SDH deficiency in ACC pathogenesis.